SCIENCE AS A CULTURAL PHENOMENON IN THE PHILOSOPHICAL HERITAGE OF S. KRYMSKYI - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article examines the socio-cultural, anthropological, praxeological aspects of functioning and development of science in philosophical concepts of the outstanding Ukrainian philosopher Serhii Krymskyi; it presents the dynamics of the philosopher’s views on science as a cultural phenomenon.